Anopheles (Cellia) rampae n. sp., alias chromosomal form K of the Oriental Maculatus Group (Diptera: Culicidae) in Southeast Asia - Somboon, Pradya; Thongwat, Damrongpan; Harbach, Ralph E. (Zootaxa, 2011)
Chromosomal form K (also known as species K) of the Anopheles maculatus group of sibling species in the Oriental Region is diagnosed and formally named An. (Cellia) rampae Harbach & Somboon, n. sp. The male genitalia, pupa and fourth-instar larva are illustrated and information is provided on the morphology, systematics, bionomics and distribution of the species.